Pemeriksa Oksigen Darah dan Denyut Nadi - Yusop, Azli; Zain, Syafiq; Nazri, Harith Danish; Ali Yusuf, Shahrul Nizam (Multidisciplinary Applied Research and Innovation, 2022)
The heart is a major and important organ in the body system. Among its important functions is that the heart pumps oxygen throughout the limbs which acts as a booster to supply energy to muscle tissue. This report introduces a prototype of an oxygen saturation and heart rate pulse as a tool to check a person ’s oxygen rate and pulse easily and anytime. Controlled using an Arduino, this prototype transmits and stores data on the device using a wireless connection (Bluetooth). The data sent were analyzed to show the heart health trends of users. However, this prototype is limited to displaying analytical values ​​and data obtained on the screen surface only. Prototype improvements are expected such as the addition of remote sensors due to the Covid-19 pandemic problem plaguing the country at the moment.